Early Transient Hypoglycemia and Test Performance in At-Risk Newborns - ElHassan, Nahed O.; Schaefer, Eric W.; Gonzalez, Basilia; Nienaber, Thomas; Brion, Luc P.; Kaiser, Jeffrey R. (American Journal of Perinatology, 2021)
Objective This study aimed to evaluate if early (within the first 3 hours after birth) transient neonatal hypoglycemia (TNH) is associated with poor academic performance in infants at-risk for hypoglycemia.Study Design This was a retrospective cohort study of at risk-infants (late preterm infants, small and large for gestational age infants, and infants of diabetic mothers [IDMs]) who were born in 1998 and 1999 at the University of Arkansas for Medical Sciences and had ≥1 recorded glucose concentration. The outcome measure was proficiency on 4th grade literacy and mathematics achievement tests. Three glucose concentration cutoffs for defining hypoglycemia (<35, <40, and <45 mg/dL) were investigated. Logistic regression models were developed to examine the association between early TNH and achievement test proficiency based on perinatal factors.Results Among 726 infants, 472 had one, 233 had two, and 21 had three risk factor(s). Early TNH (glucose concentration <35, <40, and <45 mg/dL) was observed in 6.3, 11.6, and 20.5% of the study cohort, respectively. Irrespective of the cutoff used, the frequency of early TNH (number of patients with early TNH in a risk category divided by the total number of patients in that category) was significantly greater among infants with multiple risk factors. After controlling for perinatal factors, early TNH (cutoffs <35 and <40 mg/dL) was significantly associated with decreased probability of proficiency in literacy but not mathematics. Despite that early TNH was more common in IDMs and infants with three risk factors, the category or number of risk factors did not impact academic proficiency.Conclusion Early TNH (<35 and <40 mg/dL) was associated with lower adjusted probability of proficiency on 4th grade literacy achievement tests in at-risk infants. The impact of early TNH on academic performance was similar irrespective of category or number of risk factors.Key Points
Keywords: hypoglycemia; infant of diabetic mothers; large for gestational age; small for gestational age; late preterm